Strategic marketing management in Asia : case studies and lessons across industries - Andaleeb, Syed Saad; Ḥasan, Khālid; Prabhu, Jaideep C.; Sheth, Jagdish N.; Rangan, Kasturi; Mannan, Abdul (Emerald Group Publishing Limited, 2016)
With a view to continue the current growth momentum, excel in all phases of business, and create future leadership in Asia and across the globe, there is a felt need to develop a deep understanding of the Asian business environment, and how to create effective marketing strategies that will help growing their businesses. Featuring top academics and practitioners, this book helps academics and students understand key issues, especially in the context of changing economic and related challenges in the Asian markets. Multi-industry case studies address how market opportunities need to be created, how to leverage constrained capabilities, and how to create sustainable, competitive advantage to pursue profitable growth in Asia. The case studies are drawn from across Asia, including Bangladesh, India, Sri Lanka, Malaysia, Myanmar, Pakistan, Vietnam and Singapore.